Cellular immune responses of bovine polymorphonuclear neutrophils to Calicophoron daubneyi - Silva, Liliana M. R.; López-Osorio, Sara; Peixoto, Raquel; Zhou, Ershun; Espinosa, Gabriel; Gärtner, Ulrich; Taubert, Anja; Conejeros, Iván; Hermosilla, Carlos (Frontiers in Immunology, 2025)
Calicophoron daubneyi infections have increased in Europe, being more frequent than fasciolosis in some areas. Infection occurs once definitive hosts ingest encysted metacercariae present on vegetation. Following excystation, juvenile flukes penetrate the small intestinal mucosa and migrate into the rumen where adults mature. Throughout the somatic migration, juveniles come across different microenvironments and tissues and encounter host leukocytes. Besides phagocytosis, production of reactive oxygen species (ROS) and degranulation, polymorphonuclear neutrophils also cast neutrophil extracellular traps (NETs), which can entrap several parasite species, including the closely related liver fluke Fasciola hepatica. In this study, we analyzed whether in vitro exposure of bovine neutrophils to C. daubneyi antigen (CdAg) and eggs triggered neutrophils activation and NET formation. Results on scanning electron microscopy (SEM) and immunofluorescence analyses show weak formation of short spread NETs upon CdAg stimulation, corroborated by increased extracellular DNA measurements. Likewise, early NETosis was confirmed via nuclear area expansion assays. Bovine neutrophil stimulation with CdAg 100 µg/mL concentration led to a significant increase in oxygen consumption rates (p = 0.0152) and extracellular acidification rates (p = 0.0022), while lower concentrations of CdAg (10 µg/mL) failed to induce neutrophil activation, suggesting a dose dependent response. Both intra- and extracellular ROS production was not affected by any CdAg concentration here studied. Bovine neutrophil total adenosine triphosphate concentration significantly decreased after exposure to CdAg 100 µg/mL, in line to the observed with the positive control (phorbol myristate acetate/ionomycin). In summary, C. daubneyi activates bovine neutrophils with rather weak responses, which might suggest that the release of C. daubneyi-specific molecules (i.e. excretory-secretory antigens, proteases, or nucleases) could interfere with neutrophil-related effector mechanisms. Further ex vivo analyses will clarify if such mechanisms are also involved in pathogenesis of paramphistomosis by demonstrating neutrophil recruitment into affected intestinal mucosa.